Television archives, social networks and the young audiences: The example of Internet memes as a way to revitalise public broadcasters’ engagement - Gutiérrez-Lozano, Juan Francisco; Cuartero-Naranjo, Antonio (Università della Svizzera italiana, 2023)
The purpose of this research is to explore the efforts that Spanish public television archives are making to bring their audiovisual content closer to young people via social networks. Specifically, this text focuses on analysing the public television archives of the Spanish national television company RTVE and of the Andalusian regional public television agency (RTVA), known as Archivo RTVE and MemorANDA, respectively. The methodology used is based on both qualitative and quantitative tools, consisting of content analysis and in-depth interviews. The results obtained show that both platforms manage to reach young people, but indirectly through viral videos or Internet memes. The RTVE archive is the most successful among young people because it has a more extensive collection and more resources as well as a policy that is more clearly geared towards the dissemination of its audiovisual heritage. The most negative aspect identified in this study was the repetition of regional clichés, especially in the case of MemorANDA.
Keywords: Redes sociales; Internet memes; Spain; Television archives; Social networks; Young audience; Public service